The utilization of social media as learning media for students of preservice teacher education in the pandemic of covid 19/ Lutfiyah Hidayati, Marniati and Mita Yuniati - Hidayati, Lutfiyah; Marniati,; Yuniati, Mita (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2021)
The study aims to: 1) identify the types of social media used in the learning of pre-service teacher education's students, 2) describe student perception on the use of social media in online learning. This is a descriptive research. The number of respondents was 270 students from bachelors of fashion education study program Universitas Negeri Surabaya. Data collection was carried out in July-December 2020. Method of data collection is online questionnaires and analyzed by descriptive analysis. The results of the study stated: 1) social media used in learning for pre-service teacher education's students: Whats app (100%), Youtube (80%), Pinterest (32%), Instagram (25%), and Facebook (12%); 2) Student perception on the use of social media covers how the function of social media in facilitating communication, obtaining information and academic discussion processes, generating motivation, increasing academic achievement, ease of access and use, cheap from an economic point of view, clarity and hardware support, with varying compositions of perception. The recommendation of this study is that social media as a learning media for pre-service teacher education's students is very supportive and it is recommended to use it both during the pandemic of covid-19 and after normality. It needs to be anticipated for users who are in zones that are far from the reach of electricity network and internet facilities.